Toward an energy-sensitive society: An investigation on alleviating energy poverty in Swedish neighborhoods through co-designing an energy-sensitive society - Mohammadi, Katayoun (My University, 2023)
Energy poverty (EP), the difficulty in finding a balance between energy expenditures and income in developed countries (Spirkova et al., 2016), became more severe after the Ukraine war and the resulting fuel crisis in Sweden (Platten, 2022). Although most of the alleviation methods discuss the impact of energy retrofitting projects and building performance improvement on tackling EP, the role of inhabitants is not negligible. This thesis focuses on the role of architectural design in reducing energy poverty on a neighborhood scale with a focus on social sustainability and giving active roles to people. Various methods exist to alleviate EP, from technical interventions to social considerations. However, the next step of the thesis, interviewing housing companies and experts in the field of EP, identified that only focusing on technological interventions might have paradoxical results compared to the action taken in Sweden due to the gaps in energy policies. Therefore, this thesis considered social interventions such as raising public awareness of energy poverty (EP) and promoting energy-efficient behaviors more practical for alleviating EP in Sweden at the current time. For the case study, firstly, Jättesten, located in Gothenburg, was selected as it is supposed to be a part of a pilot PED (Positive Energy Districts) project. However, the interviews demonstrated that in this neighborhood, the rate of public interest in getting involved with the co-design workshops of this thesis is low. Therefore, Hammarkullen was selected to be studied. This neighborhood struggles with social challenges like segregation, and emerging EP might worsen the problem (Sareen et al., 2022). Therefore, it is necessary to investigate EP in this area. Furthermore, as Hammarkullen’s inhabitants are willing to get involved in the research projects, engaging with them during this thesis was much more uncomplicated than with Jättesten. During this thesis’s workshops, the neighborhood was transformed into an energy-sensitive society through a co-design process with the 7th-grade students, probably most affected by EP due to being young (Churchill & Smyth, 2022), of one of the schools in Hammarkullen. An energy-sensitive society in this thesis refers to a community where people are aware of energy-efficient lifestyles, and the neighborhood itself can raise its inhabitants’ awareness of energy-related issues such as EP and its reduction methods through appropriately designed public spaces such as energy cafes and interactive artistic monuments. To meet such a co-design goal, communicating and visualizing a complicated issue such as EP was essential in making it understandable for the students. Therefore, research on visualization methods, the key to effective communication about environmental issues (Chalal et al., 2022), was done. Then, collage techniques, storyboards, and a game simulated in an augmented reality tool were selected as tools to communicate with the 7th-grade students. These adapted methods led to spontaneous conversations about energy-saving behaviors among the students in an amusing way which is an essential part of the process of teaching sustainable lifestyles. The final design results of the thesis are visualized collages of Hammarkullen as an energy-sensitive society. With the help of the students, this co-designed face of the square could be a key element in transforming Hammarkullen into a place where inhabitants can learn about energy-efficient behaviors and EP through various activities in public spaces such as energy cafes. Moreover, the design interventions in the square have adopted multiple tools and interactive artworks to combine energy-efficient behaviors with the inhabitants’ daily life and make them unconsciously aware of such behaviors. These actions could be one step forward in alleviating EP by raising awareness and giving active roles to the inhabitants.
Keywords: Energy poverty; Young people involvment; Participatory approach; Citizen engagement; Energy-saving behaviors; Raise public awareness